Natural products are the future of anticancer therapy: Preclinical and clinical advancements of Viscum album phytometabolites - Attar, R; Tabassum, S; Fayyaz, S; Ahmad, M S; Nogueira, D R; Yaylim, I; Timirci-Kahraman, O; Kucukhuseyin, O; Cacina, C; Farooqi, A A; Ismail, M (Cellular and Molecular Biology, 2015)
Cancer is a multifaceted and genomically complex disease. Research over the years has gradually provided a near complete resolution of cancer landscape and it is now known that genetic/epigenetic mutations, inactivation of tumor suppressors, Overexpression of oncogenes, spatio-temporally dysregulated intracellular signaling cascades, epithelial to mesenchymal transition (EMT), metastasis and loss of apoptosis are some of the most extensively studied biological mechanisms that underpin cancer development and progression. Increasingly it is being realized that current therapeutic interventions are becoming ineffective because of tumor heterogeneity and rapidly developing resistance against drugs. Considerable biological activities exerted by bioactive ingredients isolated from natural sources have revolutionized the field of natural product chemistry and rapid developments in preclinical studies are encouraging. Viscum album has emerged as a deeply studied natural source with substantial and multifaceted biological activities. In this review we have attempted to provide recent breakthroughs in existing scientific literature with emphasis on targeting of protein network in cancer cells. We partition this review into different sections, highlighting latest information from cell culture studies, preclinical and clinically oriented studies. We summarized how bioactive ingredients of Viscum album modulated extrinsic and intrinsic pathways in cancer cells. However, surprisingly, none of the study reported stimulatory effects on TRAIL receptors. The review provided in-depth analysis of how Viscum album modulated Endoplasmic Reticulum Stress in cancer cells and how bioactive chemicals tactfully targeted cytoskeletal machinery in cancer cells as evidenced by cell culture studies. It is noteworthy that Viscum album has entered into various phases of clinical trials, however, there are still knowledge gaps in our understanding regarding how various bioactive constituents of Viscum album modulate intracellular signaling cascades in cancer. Better and deeper comprehension oncogenic signaling cascades will prove to be helful in getting a step closer to individualized medicine.